HEALTH PROBLEMS OF PROSPECTIVE HAJJ PILGRIMS IN METRO CITY IN 2024 - Alifia, Suci; Deswara, Primadatu (Institut Agama Islam Negeri Metro, 2024)
Health during the Hajj pilgrimage is very important. Most Hajj pilgrims in Indonesia have high health risks. The purpose of the Hajj pilgrim health examination is to identify the health risk factors of Hajj pilgrims that can cause health problems while they are worshiping in the holy land. By knowing these health risk factors, control can be carried out from when the Hajj pilgrims are in their homeland until during the Hajj pilgrimage in the holy land. This descriptive study uses observation, interviews, and documentation. The Regulation of the Minister of Health (Permenkes) Number 15 of 2016 regulates the health istithaah of Hajj pilgrims, which is the main requirement for the departure of Hajj pilgrims. High-risk Hajj pilgrims are defined as Hajj pilgrims who have health conditions that epidemiologically have the potential to experience health problems. Anticipation of high-risk prospective hajj pilgrims considers that the health capability (Istithaah) of prospective hajj pilgrims is tightened to reduce the negative impact on pilgrims who are included in the high-risk category. The percentage of prospective hajj pilgrims with heart disease, lungs, mental health, diabetes, and hypertension reaches 67%.